Blast Monitoring and Blast Translation – Case Study of a Grade Improvement Project at the Fimiston Pit, Kalgoorlie, Western Australia - M Fitzgerald (The Australasian Institute of Mining and Metallurgy, 2011)
Fimiston Open Pit is operated by Kalgoorlie Consolidated Gold Mines (KCGM) as a joint venture between Barrick Gold and Newmont Mining. Over 110 years of underground mining resulted in the development of nearly 3500 km of underground workings including backfilled and open stopes up to half a million tonnes in size. These voids significantly complicate blasting processes at KCGM, influencing blast movement direction and magnitude. Blast movement monitoring to improve mine reconciliations was identified as an improvement project in the business plan for the geology team in 2008. Following successful trials in 2008 to 2009, blast monitoring and translation of ore blocks were implemented as a permanent grade control program from late 2009 and is now part of the Management Operating System (MOS) of the mine. This paper presents a summary of results from the Blast Movement Monitoring (BMM®) data collected to date. Ore blocks at KCGM are translated primarily using BMM® data. This data is obtained from the BMM® system which measures the movement of a radio transmitter installed in a blast pattern from a preblast position to a post-blast position. The application of the data collected by the BMM® tends to be both mine site and blast specific. At KCGM, an average distance obtained from the BMM® data within a given shot is the primary method used for translation. In the case that BMM® data is unavailable, a theoretical movement vector established from Orica Shotplus with distances gained from the historical BMM® database is used. Data is presented in an ore loss and dilution exercise for a bench undertaken at KCGM to understand the potential effects on reconciliations. Improvements that have flowed from implementing blast monitoring include improved reconciliations when combined with other grade control improvement projects. The increase in liaison between the geology and blast personnel at KCGM has been a significant improvement gained from the implementation of the blast monitoring program. This has allowed a better understanding of blast movement and the effects on ore dilution and ore loss by the mine geology team. In addition, the discussion of blasting tie-in plans between geology and blasting personnel has been improved which leads to more favourable blasting practices that take ore movement into account.